Ten Strengths of How Teachers Do Cooperative Learning - Jacobs, George M. (Beyond Words, 2016)
Cooperative learning involves students in working together with peers to learn, to develop learn-ing skills and to enjoy the learning process. This paper examines ten areas in which the author be-lieves he and other teachers do cooperative learning well. These areas are: (1) keeping group size small, usually four or fewer; (2) encouraging students to form heterogeneous groups; (3) monitoring groups as they cooperate and encouraging groups to rely on themselves; (4) creating tasks that the groups find challenging, but not too challenging; (5) encouraging group members to do their fair share in their groups; (6) facilitating a feeling of positive interdependence among group members; (7) being willing to try new ideas in their implementation of cooperative learning; (8) learning from their ex-periences in using cooperative learning; (9) looking for opportunities to share with colleagues about their use of cooperative learning; (10) being cooperative in their lives outside the classroom